The role of small ruminants on global climate change (Acta Scientiarum. Animal Sciences, 2018)
Global warming, as a consequence of excessive CO2 production mainly due to anthropogenic actions, is one of the main concerns of society due to the effects it can cause in the survival of humans, plants and animals. Several climatic consequences have already been reported, such as warming the oceans and changing biodiversity in various regions of the planet. One of the greenhouse gases responsible for global warming, which causes a lot of concern, is methane gas from digestion of food by ruminants. Besides that, emissions of greenhouse gases are represented also by waste management, rice cultivation, burning of residues from agriculture and soil management for agricultural production. Among ruminants, sheep and goats play an important economic role mainly in Oceania, Asia and Africa. More than 50% of small ruminants of the world are located in arid region, indicating their adaptability and future suitability to increasing temperatures. The purpose of this review is to report current knowledge about the methane emission produced by small ruminants, addressing the different interfaces of this theme, and considering possible mitigation strategies.